Effects of adding radicchio (Cichorium intybus L.) powder to rice cakes (Sulgidduk) on the quality - O, Hyeonbin; Song, Ka-Young; Zhang, Yangyang; Kim, Young-Soon (Progress in Nutrition, 2018)
This study investigated the quality, antioxidant activities, and sensory properties of Sulgidduk (rice cakes) upon the addition of radicchio (Cichorium intybus L.) powder, which is known to have antioxidant and anti-diabetic effects. Radicchio powder was freeze-dried, passed through a 40-mesh sieve, and used to replace 0%, 0.5%, 1%, 2%, 3%, or 4% of the rice flour. The content of moisture in Sulgidduk did not significantly differ among samples (p